A demonstration of how virtual meetings can enhance sustainability in a corporate context: Quantified benefits of virtual meetings through video conferencing. Issue 1 (3rd January 2018) - F. Guerin, Turlough
Abstract: Video conferencing (VC) offers benefits to businesses and organizations. A three‐month trial was undertaken across a telecommunications company in Australia to evaluate the use of VC benefits monitoring software to capture data and calculate utilization and business travel savings from air and car travel for individual VC end points across the company. The results from the trial were used by the finance and administration department of the company to promote VC usage and, at the same time, to introduce a nonessential air travel ban, which led to annualized cost savings of up to 40% on business as usual.